DETERMINATION SOME IMMUNOLOGICAL AND HISTOPATHOLOGICAL PARAMETERS RELATED WITH ROSEOMONAS MUCOSA AND ITS PIGMENT IN PHARMACEUTICAL FORMULAS. - Teeba G. Albadri; Mouruj A. Alaubydi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to conducted as a challenge test for R. mucosa ability to reduces atopic dermatitis induced in the skin of experimental animals and improve the fact that this kind of microorganism play important role as skin microflora to reduce some type of skin diseases, additionally to find the suitable pharmaceutical formula can be maintaining and stimulating bacterial isolate to produce a pigment. A probiotic application as a suitable cream formulas were prepared containing local R. mucosa biomass, Standard R. mucosa biomass and partial purified pigment to treat three groups of albino mice induced with atopic dermatitis. The main physical characteristics of the prepared cream formula are homogeneous with odorless, smooth texture, and clarity of its light yellowish color. Some immunological test including (CBC, lymphocyte, neutrophil, platelets), total serum IgE and histopathological analysis were also done. The in vivo result improve the effectivity of all prepared formulas particularly local R. mucosa biomass formula in reducing induced AD in mice either externally or internally. The findings suggested the safety of topical R. mucosa therapy of lab. animals induced with AD.